Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 1074 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Strongylura notata (Poey, 1860)" ] } The dataset includes 1074 records from 38 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0006896-160118175350007/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences